PROBLEMS OF THE VENTSPILS REGION LABOUR MARKET AND PROPOSALS FOR SITUATION IMPROVEMENT - Zivitere, Marga; Konstantinova, Elina; Oborenko, Zaiga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
There are several studies carried out on the problems of the Ventspils region labour market, but due to rapid changes in the economic situation, the results of these studies no longer accurately reflect the current situation. The aim of the paper is to present the research for identification and analysing of specific problems in the Ventspils region labour market and propose solutions for situation improvement. The research has examined the relationship between labour market change, labour market conditions and employers’ expectations in Ventspils region. The research is based on both secondary data analysis and primary data analysis obtained in a quantitative (questionnaire survey of entrepreneurs – employers) way and a qualitative way (interviews with representatives of the non-governmental sector). The analysis also showed that the main problem of the labour market related to lack of a qualified, skilled and motivated labour force. It is very important to identify opportunities for increasing qualifications and re-qualification in cooperation with educational institutions and the State Employment Agency. The problem was also the employment of persons before retirement and persons with disabilities. Therefore, there are necessary new, more effective mechanisms of involvement of these groups in the labour market, which are based on cooperation with NGOs, continuing education possibilities and social entrepreneurship. The role of the municipality is very important in this process.